Minimum safety protection distance of high‐pressure natural gas pipeline based on physical explosion injury consequences - Yuqing Liu; Yazhe Zhou; Wenshu Wang; Shanshan Tian; Yawei Zhou; Na Gao; Karyal Kazman (Engineering Reports)
Abstract The transportation of natural gas through pipelines offers numerous advantages. However, physical explosions in high‐pressure natural gas pipelines can cause casualties and property loss. There is currently no method for accurately predicting the damage range of physical explosions in pipelines, and a safer site selection plan cannot be determined during the pipeline construction design stage. This study proposes a method for determining the range of pipeline physical explosion damage by comprehensively considering two factors: the size range of the physical explosion craters, and the attenuation distance of the shock waves. A high‐pressure natural gas pipeline physical explosion crater model was constructed using HyperMesh software, and the accuracy of the model was verified using the PRCI calculation model. Based on the Sadovsky formula, a program was developed to simulate the spatiotemporal changes in shock wave diffusion, demonstrating the law of shock wave diffusion. The results show that the distance from the overpressure peak attenuation of the physical explosion shock wave in air to 0.02 MPa is calculated to be 33 m, and the maximum damage range of the crater is 9.27 m. Finally, the safe protection distance for personnel and buildings was determined to be 33 m.